2019
DOI: 10.1002/mc.23106
|View full text |Cite
|
Sign up to set email alerts
|

p53 Promotes chemoresponsiveness by regulating hexokinase II gene transcription and metabolic reprogramming in epithelial ovarian cancer

Abstract: Metabolic reprogramming (including the Warburg effect) is a hallmark of cancer, yet the association between the altered metabolism and chemoresistance remains elusive. Hexokinase II (HKII) is a key metabolic enzyme and is upregulated in multiple cancers. In this study, we examined the impact of targeting metabolism via silencing of HKII on chemoresistance in ovarian cancer (OVCA). In addition, the regulatory molecular mechanism of tumor metabolism was examined using gain‐ and loss‐of‐function approaches in epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…The chemosensitizing effect of metformin seems to be correlated with p53 function. In the presence of p53 , metformin suppresses hexokinase II (glycolytic enzyme) and pyruvate dehydrogenase kinase (anti-apoptotic serine/threonine kinase) [ 72 ]. As a result, EOC cells are sensitized to metformin.…”
Section: Metformin and Ovarian Cancermentioning
confidence: 99%
“…The chemosensitizing effect of metformin seems to be correlated with p53 function. In the presence of p53 , metformin suppresses hexokinase II (glycolytic enzyme) and pyruvate dehydrogenase kinase (anti-apoptotic serine/threonine kinase) [ 72 ]. As a result, EOC cells are sensitized to metformin.…”
Section: Metformin and Ovarian Cancermentioning
confidence: 99%
“…Although the mechanism of the Warburg effect is still unclear, it is believed that the relevant mechanisms may include mitochondrial dysfunction, hypoxia, tumor gene signaling, and abnormal expression of certain metabolic enzymes. Some studies have shown that hexokinase was overexpressed in tumor cells, among which GLUT1 plays a key role in initiating and maintaining the high glucose catabolic rate required for the rapid growth of tumor cells [15] . To elucidate the role of LH‐20‐15 in glycometabolism, the expression levels of GLUT1, HK2, and LDHA were examined by using Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…TP53 is a well-known tumor suppressor that induces growth arrest or apoptosis and involved in cell cycle regulation. 28 TP53 is downregulated in many types of tumors including non-small cell lung cancer, colorectal cancer, cervical cancer and ovarian cancer, [29][30][31][32][33][34] which can lead to a poor survival rate. Our results showed that TP53 was downregulated in OC tissues, and could be decreased by miR-183-5p mimics and restored by overexpressed LEMD1-AS1, respectively.…”
Section: Discussionmentioning
confidence: 99%